SINERGI ANTARA PEMERINTAH KOTA PEKANBARU DAN POLRESTA DALAM MELAKUKAN PENERTIBAN TEMPAT HIBURAN MALAM TAHUN 2020 - Muhammad Munawir; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Pekanbaru City as one of the Metropolitan cities whose people need a means to relieve fatigue from their daily activities. Thus the city of Pekanbaru has a place of public entertainment. Pekanbaru as one of the developing cities, has become one of the attractive industrial locations for business people, one of the rapidly growing industrial sectors in Pekanbaru at this time is the night club. The night club is a means of relaxing and also one of the tourist destinations in the metropolitan city. However, nightclubs violate the rules and regulations set by the government. So it is necessary to bring order to the police and the Pekanbaru city government to maintain order in the community. The formulation of this research is